Moderasi Kesesuaian Tingkat Keterampilan, Interkoneksi, dan Organizational Innovativeness Terhadap Efektivitas Sistem Informasi Akuntansi - Kresnandra, Anak Agung Ngurah Agung; Anggara, I Wayan Gde Wahyu Purna (E-Jurnal Akuntansi; Vol 32 No 8 (2022), 2022)
This study aims to determine the effect of Accounting Information Systems on individual performance and the moderating effect of skill level suitability, interconnection, and organizational innovativeness variables on individual performance. The research was conducted at the Office of the Ministry of Religion in Bali Province. The research population is the employees of the Ministry of Religion Office in Bali Province. The sample was determined by purposive sampling method with a sample of 73 employees as respondents. The analysis technique used is Moderated Regression Analysis. The results show that the effectiveness of the use of accounting information systems has a positive effect on individual performance, skill level strengthens the effect of the effectiveness of the use of accounting information systems on individual performance, interconnection does not moderate the effect of the effectiveness of using accounting information systems on individual performance and organizational innovativeness strengthens the effect of the effectiveness of using information systems. accounting for individual performance. Keywords: AIS Effectiveness, Skill Level Match, Interconnection, Organizational Innovativeness, Individual Performance.